The teachers’ training and probationary period, the thought of Salerno newly hired teachers: a case study - Calenda, Marika; Tammaro, Rosanna (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
We present a research done in the province of Salerno. We describe the results of the analysis of the variable of the model training structure, conducted in order to understand how it was received the model training provided by the law 107/2015. The variable was operationalized in two aspects, the global one and that relative to the different phases. In accord to Lucisano-Salerni (2002), the research results were developed in the following points: objectives and problem analysis, methodology, presentation and discussion of results, conclusions and perspectives of future research. The main transactions carried out in this research are: the definition of the unit of analysis, the purpose and the contest, the achieved sample, the survey instrument used, the coding level and recode variables, the procedures for data analysis.